Conference Report: 4th Global CRO Council for Bioanalysis: coadministered drugs stability, EMA/US FDA Guidelines, 483s and Carryover. (April 2012) - Lowes, Steve; Jersey, Jim; Shoup, Ronald; Garofolo, Fabio; Needham, Shane; Couerbe, Philippe; Lansing, Tim; Bhatti, Masood; Sheldon, Curtis; Hayes, Roger; Islam, Rafiq; Lin, Zhongping (John); et al.
The Global CRO Council for Bioanalysis (GCC) was formed in September 2010. Since then, the representatives of the member companies come together periodically to openly discuss bioanalysis and the regulatory challenges unique to the outsourcing industry. The 4th GCC Closed Forum brought together experts from bioanalytical CROs to share and discuss recent issues in regulated bioanalysis, such as the impact of coadministered drugs on stability, some differences between European Medicines Agency and US FDA bioanalytical guidance documents and lessons learned following recent Untitled Letters. Recent 483s and agency findings, as well as issues on method carryover, were also part of the topics discussed.